Over-land trucking and freight : relevant costs for decision making - Albright, Thomas L., 1955-; Juras, Paul E.; Elrod, Russ (London : SAGE Publications Ltd, 2017)
Over-land trucking and freight has a long-established and mutually beneficial business relationship with a major international automotive parts company, FHP Technologies. Management at FHP has approached Over-land with a request to provide additional routes that are important to the efficiency of its supply chain. Over-land's management wishes to nurture the business relationship with FHP but is concerned about the available capacity to service the new routes, potential risks, and profitability associated with FHP's request.
Originally Published InAlbright, T. J., Juras, P., & Elrod, R. (2014). Over-land trucking and freight: Relevant costs for decision making. IMA Educational Case Journal, 7(2), Article 2.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Over-land trucking and freight -- Case studies; Cost accounting -- Case studies; Decision making -- Case studies